Validasi Metode Analisis Iodin Secara Spektrofotometri UV-Vis pada Dua Variasi Pelarut: Validation of The Method of Iodin Analysis by Uv-Vis Spectrofotometry with Two Variations of Solution - Abdilah, Fauzi; Karina Aulia Rahmawati; Widya Tresna Dewi; Keryanti; Hulupi, Mentik (KOVALEN: Jurnal Riset Kimia, 2023)
In this study, the method of analysis of iodine by UV-Vis spectrophotometry was validated. Two other solvents, ethanol, and cyclohexane were used to validate this approach. The UV-Vis Spectrophotometer method's linearity, detection, and quantization limitations, precision, and accuracy were investigated as variables. The results of the linearity tests indicated that the method was proportionally verified because the r values for the two iodine solutions in ethanol and cyclohexane varied between 0.990 and 0.999, respectively. This suggests that the values were higher than 0.99. The LOD values for the ethanol solvent were 4.441 mg/kg and the LOQ was 14.802 mg/kg, whereas the cyclohexane solvent had an LOD value of 2.660 mg/kg and the LOQ was 8.866 mg/kg. According to the required precision acceptance, the %RSD value of 2%, precision values for both standard iodine solutions with two modifications of solvents demonstrated good results. Recovery percentages of ethanol solvents are 96% and cyclohexane solvents are 86%, respectively, according to accuracy measurements. The combined uncertainty value for this test is 0.109 for the ethanol solvent and 0.019 for the cyclohexane solvent, respectively. This research provides a comprehensive understanding of the validity of the iodine analysis method, establishing a robust foundation for the sustainability and reliability of using UV-Vis spectrophotometer in the analysis